Are U‐Th Dates Correlated With Historical Records of Earthquakes? Constraints From Coseismic Carbonate Veins Within the North Anatolian Fault Zone. Issue 7 (22nd July 2019) - Karabacak, Volkan; Uysal, I. Tonguç; Mutlu, Halim; Ünal‐İmer, Ezgi and Dirik, R. Kadir and Feng, Yue‐xing and Akıska, Sinan and Aydoğdu, İsmail and Zhao, Jian‐xin
Abstract: U‐Th dating of carbonate veins in connection with active tectonics has recently been used as an attractive tool for constraining the absolute timing of late Quaternary crustal deformations. In this study, for the first time we correlate U‐Th ages of travertine deposits in coseismic fissures along the North Anatolian Fault Zone with records of paleoseismological studies supported by historical earthquake catalogued data. U‐Th ages are assessed in relation to the recurrence interval and the size and epicenter distance of major Holocene earthquakes. Our statistical evaluations on age correlations indicate that the carbonate vein precipitation is concentrated in eight different periods along the North Anatolian Fault Zone. The periods are well correlated with historical earthquake records and with previous dating results of the nearby trench studies. At least six of the periods correspond to the earthquakes reported in the historical catalogues. The age correlations of carbonate precipitation intervals for the last millennium show a recurrence along the eastern North Anatolian Fault Zone with a mode at 130–330 years that is consistent with a previously proposed paleoseismic recurrence interval of the fault. Recorded events in carbonate veins indicate a close‐epicenter ( d < 200 km) and high‐intensity (I > VI) paleoearthquakes. Our results suggest that coseismic carbonate veins could be used to determine paleoseismic records as a supplementary tool to augment paleoseismological techniques. This tool has advantages over traditional paleoseismological methods for the understanding of long‐term earthquake behavior, particularly for prehistoric late Pleistocene events which cannot be dated easily by traditional paleoseismological methods. Key Points: Age distributions of coseismic carbonate veins are comparable with historical earthquakes Coseismic carbonates are precipitated with the close‐epicenter ( d < 200 km) and high‐intensity (I > VI) earthquakes Coseismic carbonates are a good candidate to determine the long‐term seismic release records